Danzirly - Muñoz, Gloria, 1987- (Book collections on Project MUSE., 2021)
"Danzirly is a stunning bilingual poetry collection that considers multigenerational Latinx identities in the rapidly changing United States. Winner of the Academy of American Poets' Ambroggio Prize, Gloria Muñoz's collection is an unforgettable reckoning of the grief and beauty that pulses through twenty-first-century America."--Provided by publisher.